Amniotic membrane versus platelet-rich fibrin in treatment of gingival recession- a randomized control trial - M.P. Chaitra; Shrinidhi Maji Shankar; T.P. Shivakumar; Soumya B. Gururaj; Chethana K. Chidambar; Kala S. Bhushan (Elsevier, 2024)
Objective: To determine the efficacy of latelet-rich fibrin (PRF) and Amniotic membrane (AM) along with the coronally advanced flap (CAF) technique in treating Miller's class I gingival recession (GR) defects. Material and methods: A total of 32 sites with Miller's class I GR defects were distributed into Group A (CAF + PRF, n = 16) and Group B (CAF + AM, n = 16). Clinical parameters like gingival index (GI), plaque index (PI), gingival bleeding index (GBI), gingival sulcus depth (GSD), relative attachment level (RAL), and gingival marginal level (GML) were measured at baseline and at 3, 6 and 9 months after surgical intervention. Results: PRF and AM with CAF were effective treatment modalities for treating Miller's class I GR defects, with an average root coverage value of 2.00 ± 0.75 mm in Group A and 1.5 ± 0.3 mm in Group B. Complete coverage (100 %) was obtained in 57 % sites of group A and 49 % sites of group B. At the 9-month follow-up, there was a significant increase in relative attachment levels in both groups when compared to baseline. Conclusion: In the present study it was observed that there was a clinically and statistically significant improvement in root coverage with both groups. PRF-treated sites showed > 50 % complete coverage and hence were superior. AM showed comparable results to PRF and could be used as an alternative.